On the road to Durban:using empowerment evaluation to grow teachers' arts and culture curriculum knowledge - Glass, Donald L. (My University, 2008)
South Africa has engaged in an outcomes-based curriculum innovation that includes Arts and Culture as a new learning area. Few empirical studies have examined what the curriculum innovation looks like in practice in this high inequity and low capacity school system. This study examines what teachers' curriculum looked like, what influenced their design decisions, and what the growth of their curriculum knowledge looked like. A small sample of new grade 7 Arts and Culture teachers from a disadvantaged township setting participated in an adaptation of empowerment evaluation to gather curriculum data over a 1.5 year period. The findings of this evaluation-research study showed teachers using a more dialogic process to design curriculum with varied influences from policy, learning support materials, and handson arts practice, rather than a linear design process starting with learning outcomes. Gaps in curriculum knowledge about outcomes and assessment were also identified. As part of the empowerment curriculum evaluation (ECE), learning outcomes seemed to play a more powerful role as heuristics in growing their meaning(s) in practice, and generating valid assessment critiera. Evidence was found to argue that the ECE was associated with curriculum knowledge growth and increased self-determination for the teachers who had some initial experience in the learning area before participating in the study. iv
Keywords: Art; Education; Curriculum; Evaluation; Design; Empowerment; Outcomes; C2005; South Africa